Hubungan Neutrophil-Lymphocyte Ratio dengan Kejadian Deep Vein Thrombosis Berdasarkan Temuan Ultrasonografi Periode Tahun 2022-2024 di RSUP Haji Adam Malik Medan - Muhammad Farhansyah Pane; Henny Maisara Sipahutar; Dairion Gatot; Netty Delvrita Lubis; Dedy Dwi Putra; Taufik Ashar (Jurnal Pengabdian Ilmu Kesehatan, 2026)
Deep vein thrombosis (DVT) demonstrates a complex correlation between thrombosis formation and inflammation, leukocytes (monocytes, lymphocytes, and neutrophils), and platelets, indicating the potential contribution of blood cellular components to the initiation and spread of DVT. Therefore, Neutrophil-Lymphocyte Ratio (NLR) has potential as a diagnostic marker for DVT. This study aimed to evaluate the relationship of NLR to the occurrence of DVT based on ultrasonography (USG) findings. This study was a retrospective, cross-sectional analytical study conducted at medical records department of Haji Adam Malik General Hospital, Medan, of patients with DVT who underwent USG and complete blood counts examination over a 2-years period, from 2022 to 2024. Descriptive statistical analysis was used to determine frequency distribution of demographic data. Inferential statistical analysis was performed to assess correlation between two variables. To determine the ability of NLR as a diagnostic marker for DVT, a Receiver Operating Characteristic (ROC) curve analysis was performed. The NLR value was significantly higher in DVT group (10.26 ± 8.51 vs. 4.26 ± 3.15; p < 0.001). The association between NLR and DVT incidence was statistically significant (p < 0.001), with patients with an NLR ≥4.35 having a 1.747-fold greater risk of developing DVT compared to patients with an NLR below that threshold. The best cutoff value for NLR as a DVT diagnostic tool was 4.35, with a sensitivity of 72.7%, specificity of 66.7%, a positive predictive value (PPV) of 82.8%, a negative predictive value (NPV) of 52.6%, with a diagnostic accuracy of 70.8%. NLR is a simple, inexpensive, and readily accessible inflammatory biomarker that can aid in risk stratification or an initial diagnostic approach to DVT.